Folgen des Mindestlohns für ausländische und deutsche Beschäftigte - Clemens Ohlert; Juliane Pehla (Wirtschaftsdienst, 2025)
Weil ausländische Beschäftigte in Deutschland zu einem größeren Anteil im Niedriglohnbereich arbeiten, profitieren diese überdurchschnittlich häufig von Anhebungen des Mindestlohns. Allerdings ging mit der Anhebung auf 12 exteuro im Oktober 2022 auch die Arbeitszeit ausländischer Beschäftigter im Mindestlohnbereich zurück. Der Anstieg der monatlichen Verdienste fiel deshalb weniger stark aus als der Anstieg der Stundenlöhne. – – This article examines the employment of foreign workers in the minimum wage and low wage sectors in 2022 and 2023 based on the earnings survey conducted by the Federal Statistical Office. It shows that foreign workers are significantly overrepresented in these wage sectors in Germany. Following the increase in minimum wage to 12 exteuro in 2022, workers in the minimum wage sector show a very strong development in hourly wages from 2022 to 2023, with little difference between German and non-German nationals. The development of monthly earnings was weaker overall than that of hourly wages and was lower for foreign employees than for German employees. This development is related to a decline in the average weekly working hours of employees in the minimum wage range.
Keywords: J15; J21; J31; 330